FELINE PANLEUKOPENIA VIRUS INFECTION: A COMPREHENSIVE REVIEW (2010–2025) - H.J. Apoorva; V.S. Lathamani; P.T. Ramesh; Shivaraj B. Murag; R. Sudharani; M.P. Veena (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Feline panleukopenia (FPL) is a highly contagious viral disease caused by feline panleukopenia virus (FPV), affecting cats across all age groups. FPV is classified under Carnivore Protoparvovirus 1, within the genus Protoparvovirus of the Parvoviridae family, which includes three subfamilies: Parvovirinae, Densovirinae and Hamaparvovirinae. Clinical severity varies with age, immune competence and the presence of secondary infections. Typical signs include lethargy, anorexia, fever, vomiting, diarrhea, and leukopenia. Diagnosis is based on clinical signs and hematological findings, confirmed through polymerase chain reaction (PCR) or rapid antigen detection kits. Recent diagnostic advances, such as nano-PCR and isothermal amplification techniques, have enhanced detection speed and sensitivity. Treatment is supportive, as no specific antiviral exists. Core interventions include intravenous fluids, electrolyte correction, antiemetics, and broad-spectrum antibiotics to manage secondary bacterial infections. Nutritional support is vital for recovery. In severe cases, blood transfusions or immunomodulators such as interferon-omega or granulocyte colony-stimulating factor (G-CSF) may be indicated. Early intervention and strict biosecurity are critical for successful outcomes and disease control.